EP 74. Comparison of freehand B-mode and power-mode 3D ultrasound for visualisation and grading of internal carotid artery stenosis. Issue 9 (September 2016) - Weinreich, A.; Saur, D.; Pelz, J.
Abstract : Background: Currently, colour-coded duplex sonography (2D-CDS) is clinical standard for detection and grading of ICAS (1,  2) as a relevant risk factor for ischaemic stroke (3,  4). Unlike angiographic imaging modalities, 2D-CDS assesses ICAS by its haemodynamic effects rather than luminal changes 1 . Therefore, aim of this study was to evaluate freehand 3D ultrasound (3DUS) for direct visualisation and quantification of ICAS. Methods: 37 patients with 43 ICAS were examined with 2D-CDS as reference standard and with freehand B-mode respectively power-mode 3DUS. For 3DUS Curefab CS (Curefab Technologies GmbH, Munich, Germany) was used. While 3DUS scanning was done by one examiner, ICAS were manually reconstructed within the virtual 3D-volume and graded by 2 physicians. Stenotic value of 3D reconstructed ICAS was assessed by calculating distal diameter and distal cross-sectional area (CSA) reduction percentage. Results: There was a trend but no significant difference in successful 3D reconstruction of ICAS between B-mode and power mode (examiner 1 [Ex1] 81% versus 93%, examiner 2 [Ex2] 84% versus 88%). Interrater reliability (IR) was best for power-mode 3DUS and assessment of stenotic value as distal CSA reduction percentage (intraclass correlation coefficient [ICC] 0.90) followed by power-mode 3DUS and distal diameter reduction (ICC 0.81). IR was poor for B-mode 3DUS (ICC, distal CSA reduction 0.36; distal diameter reduction 0.51). In comparison to 2D-CDS intermethod reliability was clearly better for power-mode 3DUS (ICC, distal diameter reduction: Ex1 0.85, Ex2 0.78; ICC, distal CSA reduction: Ex1 0.63, Ex2 0.57) than for B-mode 3DUS (ICC, distal diameter reduction: Ex1 0.40, Ex2 0.52; ICC, distal CSA reduction: Ex1 0.15, Ex2 0.51). For power-mode 3DUS (distal diameter reduction) positive predictive value for differentiation between moderate and high-grade ICAS was 0.81 (Ex1) and 0.76 (Ex2) while negative predictive value was 0.92 (Ex1) and 0.91 (Ex2). Conclusions: Power-mode 3DUS is superior to B-mode 3DUS for imaging and quantification of ICAS. It might ideally complement 2D-CDS as initial vascular diagnostic in stroke patients and could be a simple alternative for more invasive and time-consuming imaging modalities like computed tomography angiography or contrast-enhanced magnetic resonance angiography.